2015
DOI: 10.1016/j.actbio.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Field effect transistors based on semiconductive microbially synthesized chalcogenide nanofibers

Abstract: Microbial redox activity offers a potentially transformative approach to the low-temperature synthesis of nanostructured inorganic materials. Diverse strains of the dissimilatory metal-reducing bacteria Shewanella are known to produce photoactive filamentous arsenic sulfide nanomaterials by reducing arsenate and thiosulfate in anaerobic culture conditions. Here we report in situ microscopic observations and measure the thermally activated (79 kJ mol(-1)) precipitation kinetics of high yield (504 mg per liter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…ANA‐3 is known to synthesize nanofibres of arsenic sulfide, as shown in Fig. C and previously reported (McFarlane et al ., ). The shape of the material was influenced by the microorganism expressing the reductase genes.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…ANA‐3 is known to synthesize nanofibres of arsenic sulfide, as shown in Fig. C and previously reported (McFarlane et al ., ). The shape of the material was influenced by the microorganism expressing the reductase genes.…”
Section: Resultsmentioning
confidence: 97%
“…The diffrations patterns revealed overlapping crystalline phases that were produced by both E. coli and ANA‐3, such as orpiment (As 2 S 3 ), realgar (AsS) and alacranite (As 8 S 9 ). Previous reports have observed that the arsenic sulfide material crystallinity improves moderately over a period of time (Lee et al ., ; McFarlane et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The nanotubes (20 to 100 nm by ca. 30 µm) form extracellular networks, that upon aging are not only electrically conductive but also exhibit photoluminescence, photoactive, and transistor-like properties (5, 7). …”
Section: Microbial Deposition Of Metallic and Semimetallic Electronicmentioning
confidence: 99%